Psychometric validation of the Bengali version of the 10 item MARS(Medication Adherence Rating Scale) among bipolar disorder patients, Kolkata West Bengal. (Indian Journal of Public Health Research & Development, 2025)
Background: Bipolar affective is a chronic mental illness, where recurrence is very common .Bipolar patients have low or partial  adherence rate to treatment. The MARS is a 10 item self report measure of medication compliance. Medication adherence is a vital predictor of illness course and outcome  in patients with bipolar disorder.Aim: 1. To validate the English to Bengali translation of MARS.• To establish the reliability of the MARS scale.Material and Method: The original scale was translated to Bengali version by the following process:• Establishment of a bilingual group of experts.2. Examination of the conceptual structure of the instrument under study by the experts. 3. Translation 4. Examination of the translation by the experts. 5. Examination of the translation by a monolingual group. 6. Blind back translation7. Examination of the blind back translation by the experts.The Psychometric properties of MARS-B were validated among the bipolar patients (N=100).Data were collected during the period of May 2023 to July2023.by interviewing with simple random sampling and analyzed by statistical package of social science(SPSS -16) and MS Excel 2010 version software.Results:This study report shows good reliability Cronbach’s (α) 0.71 of MARS (Bengali) version. principal-components analysis extracted four factors from the MARS that together accounted for 55% of the variance. These factors were then subjected to a Varimax rotation revealing the factors of ‘Medication adherence behavior’, ‘Health status and wellbeing causes medication adherence’, ‘Perception  regarding benefits of medication adherence’,and ‘Negative side effects towards psychotropic medication’ . Conclusion: This study shows that MARS Bengali version is valid, reliable and applicable in clinical practice, research, public health and primary health care in west Bengal.
Keywords: Medication adherence rating scale, bipolar disorder, adherence, compliance.